Bibliometric analysis of traditional Chinese exercises in stroke rehabilitation from 2003 to 2022 using CiteSpace - Li, Xiaoyi; Li, Zhi; Wang, Hongxing (Frontiers in Neurology, 2024)
Background: A comprehensive analysis was conducted on the relevant literature pertaining to the application of traditional Chinese exercises in stroke rehabilitation over the past 20 years, Additionally, a scientific knowledge map was created to elucidate the current research status, investigate its development process and research trends, and offer novel research perspectives for future studies.Methods: Data from the core collection of WOS and CiteSpace was utilized to analyze the relevant literature on traditional Chinese exercises in stroke rehabilitation. The analysis began with the selection of publications, countries, institutions, highly-cited authors, and co-cited references to summarize the current research status of traditional exercises in stroke rehabilitation. Secondly, keywords were employed to identify research hotspots, and keyword clustering time zone diagrams were chosen to track the research development process. Lastly, burst keywords were employed to explore the research frontiers and trends in this field.In total, 937 documents were retrieved, and the annual publication volume consistently and sustainably increased. China and the USA emerged as significant contributors. The Chinese University of Hong Kong had the highest publication count, with ADA L from The University of Sydney being a highly-cited author. Initially, This is a provisional file, not the final typeset article keywords focused on cardiac output, blood flow, pressure, and performance. Over time, the focus shifted to heart failure, muscle strength, mortality, and exercise capacity. Current trends encompass outcome, impact, virtual reality, and anxiety. Conclusion: It is essential to integrate key elements of traditional exercise approaches with the specific attributes of movement disorders during the stroke recovery phase. Therefore, enhancing the stroke rehabilitation training program and exploring novel avenues for traditional exercise-based interventions are critical.